ANALISA ISI LAMBUNG DAN BIOLOGI REPRODUKSI IKAN SELAIS TENGGARAI (KRYPTOPTERUS APOGON) DI DANAU BARU DESA BULUHCINA KECAMATAN SIAK HULU KABUPATEN KAMPAR PROVINSI RIAU - Rizky Ulva; Windarti Windarti; Eni Sumiarsih (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
Kryptopterus apogon is one of the freshwater fishes that inhabit the Danau Baru oxbow lake. This study aimed to understand the stomach content of the fish living in the lake and also to understand its reproductive biology during the period of December-February 2017.The number of fish captured were 45 fishes ( 24 females and 21 males). The stomach content was analyzed using a gravimetry method, while its reproductive biology was noted. K. apogon is as carnivorous fish and the types of food present in the stomach was fish (98.644%) as main food, crustaceans (0.940%) and insects (0.001%) as additional food. Mature fishes (13 females and 14 males) present throughout the research period, but the peak of reproductive activities occurred in February. The Maturity Index of female ranged from 0.09-5.45% and that of the male was 0.07-0.18%. The fecundity of the fish was 36.075-540.72 eggs (in 340-690 mm TL and 197.5-1.725 gr BW females). This fish is total spawner, and the diameter of eggs from the anterior, middle and posterior parts of the ovary was around 0.866 mm. These fish tend to consume fish during its gonad development.